Evaluación de la calidad de atención de enfermería a los pacientes internados en el Hospital Básico Yantzaza. Periodo mayo a agosto del 2015 - Agreda Pardo, Bethy Maricel (2016)
The present study had as purpose to assess the quality of nursing care patients in the Yantzaza basic Hospital in the period May to August 2015, so using the survey technique applied a questionnaire 62 patients admitted for more than 3 days and that they were willing to participate. The study used the following types of research; observational, prospective, transversal, descriptive and bibliographical. The results on the quality of perceived nursing care were: nurses sometimes presents the user with a 43%, 61% of the staff does not provide information to the user about the service facilities, 37% concerned that almost always staff provides information and confidence before and during the performance of procedures, 47% almost always staff comes to the user with respect and kindness 29% of users sometimes have received guidance on treatment effects, 37% sometimes have received explanation of post-treatment preventive care, 40% of users have received ongoing attention with sufficient and necessary time, 39% refer that they almost always respect their beliefs and customs, 34% of users refirieren to staff to encourage them to express feelings and concerns. 37% almost always refers relatives receive cordial attention, in terms of perception in general users about services received refer, 34% that care is very good, after analyzing these results the author developing a plan of action to improve the quality of care, which I base on the socialization of the obtained results, conferences, motivational and delivery of NANDA diagnoses information guide. Keywords: assessment, quality nursing, patient hospitalized, basic Hospital care